Gene drive to reduce malaria transmission in sub-Saharan Africa. (24th January 2018) - Burt, Austin; Coulibaly, Mamadou; Crisanti, Andrea; Diabate, Abdoulaye; Kayondo, Jonathan K.
ABSTRACT: Despite impressive progress, malaria continues to impose a substantial burden of mortality and morbidity, particularly in sub-Saharan Africa, and new tools will be needed to achieve elimination. Gene drive is a natural process by which some genes are inherited at a greater-than-Mendelian rate and can spread through a population even if they cause harm to the organisms carrying them. Many different synthetic gene drive systems have been proposed to suppress the number of mosquitoes and/or reduce vector competence. As with any control measure, due attention should be paid to the possible evolution of resistance. No gene drive construct has yet been reported that is 'field-ready' for release, and when such constructs are developed, they should be assessed on a case-by-case basis. Gene drive approaches to vector control promise to have a number of key features that motivate their continued development, and scrutiny, by all concerned.